Analisis Paparan Bahaya pada Operasional Work Over dan Well Services pada Sumur X Menggunakan Metode HIRADC - Prayugo, Dody; Parji, Parji; Lukman, Lukman (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Operational work activities of Work Over and Well Service in oil and gas companies are carried out to maintain optimal wells, this work is not free from high hazard exposure that can pose a risk to workers. Therefore, handling is needed to reduce exposure to hazards. This study aims to identify, assess, and provide control solutions to hazards in Work Over and Well Service operations in oil and gas drilling wells. Therefore, the Hazard Identification Risk Assessment and Determining Control (HIRADC) method is used. To achieve the study's objectives, data collection was carried out using observation and interview methods. The results of this study obtained 37 hazard findings with 27 values ​​at the High risk level, and 10 values ​​at the moderate risk level in 15 Work Over and Well Service work activities. Then the control determination is given based on the control hierarchy, namely elimination, substitution, engineering, administration, and personal protective equipment so that all risk levels drop to low.